2021
DOI: 10.15420/ecr.2021.26
|View full text |Cite
|
Sign up to set email alerts
|

Asian Pacific Society of Cardiology Consensus Recommendations for Pre-participation Screening in Young Competitive Athletes

Abstract: Sports-related sudden cardiac death is a rare but devastating consequence of sports participation. Certain pathologies underlying sports-related sudden cardiac death could have been picked up pre-participation and the affected athletes advised on appropriate preventive measures and/or suitability for training or competition. However, mass screening efforts – especially in healthy young populations – are fraught with challenges, most notably the need to balance scarce medical resources and sustainability of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…In Asian countries, research regarding SrSCD is scarce and not very thorough. For example, the prevalence of SrSCD in Singapore is only about 86.7%, which was 72 out of 83 patients [7]. Recent research showed that the increased risk of CVDs in athletes is associated with several factors [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Asian countries, research regarding SrSCD is scarce and not very thorough. For example, the prevalence of SrSCD in Singapore is only about 86.7%, which was 72 out of 83 patients [7]. Recent research showed that the increased risk of CVDs in athletes is associated with several factors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HCM often may be asymptomatic at the time of diagnosis (Maron, 2018 ). Medical societies and sport associations recommend screening programs for athletes to prevent SCD (Corrado et al, 2005 ; Drezner et al, 2016 ; Fritsch et al, 2017 ; Maron et al, 2014 ; Maron et al, 2015 ; Mont et al, 2017 ; Wang et al, 2021 ). Standard 12‐lead electrocardiogram (ECG), next to medical history and physical examination, is included in all guidelines as a basic screening tool.…”
mentioning
confidence: 99%